Severe Gastrooesophageal Reflux Disease Associated with Foetal Alcohol Syndrome - N. K. Sujay; Matthew Jones; Emma Whittle; Helen Murphy; Marcus K. H. Auth (Case Reports in Pediatrics)
Prenatal alcohol exposure may have adverse effects on the developing foetus resulting in significant growth restriction, characteristic craniofacial features, and central nervous system dysfunction. The toxic effects of alcohol on the developing brain are well recognised. However, little is known about the effects of alcohol on the developing gastrointestinal tract or their mechanism. There are few case reports showing an association between foetal alcohol syndrome and gastrointestinal neuropathy. We report a rare association between foetal alcohol syndrome and severe gastrooesophageal reflux disease in an infant who ultimately required fundoplication to optimise her growth and nutrition. The child had failed to respond to maximal medical treatment (domperidone and omeprazole), high calorie feeds, PEG feeding, or total parenteral nutrition. The effect of alcohol on the developing foetus is not limited to the central nervous system but also can have varied and devastating effects on the gastrointestinal tract.